Diagnosis Of Functional Disorders Of The Temporomandibular Joint In Distal Occlusion And Their Comprehensive Treatment (Academicia Review-A Multidisciplinary Online Journal, 2026)
Distal occlusion is one of the most common dentofacial anomalies and is frequently associated with functional disorders of the temporomandibular joint (TMJ). Changes in mandibular position, imbalance of the masticatory muscles, and altered occlusal relationships may lead to pain, joint dysfunction, limited mandibular movement, and pathological joint sounds. Early diagnosis and comprehensive treatment are essential for restoring functional balance and preventing chronic complications. This article discusses modern diagnostic methods for TMJ disorders associated with distal occlusion and presents comprehensive therapeutic approaches, including orthodontic, orthopedic, physiotherapeutic, and occlusal rehabilitation methods. The study emphasizes the importance of an interdisciplinary approach in achieving stable functional and aesthetic outcomes.
Keywords: Distal occlusion; temporomandibular joint; TMJ dysfunction